Evidence for a possible life-cycle association between Syracosphaera protrudens (heterococcolithophore) and Syracosphaera pulchra HOL pirus-type (holococcolithophore) - Triantaphyllou, M.; Dimiza, M.; Malinverno, E.; Young, J.R. (Journal of Micropalaeontology, 2009)
An apparently unambiguous combination coccosphere from the Eastern Mediterranean (Aegean Sea, Greece) is documented involving Syracosphaera protrudens Okada & McIntyre,  1977 and Syracosphaera pulchra Lohmann, 1902 HOL pirus-type. This finding is difficult to interpret in terms of the current understanding of Syracosphaera taxonomy and adds evidence to the hypothesis of a distinctly complex Syracosphaera pulchra life cycle.